Perspektif siswa terhadap dunia kerja pada program praktik kerja lapangan di SMKN 1 cempaga hulu - Alamsyah, Fajar; Sholichah, Nikmatus (Jurnal Madako Education, 2025)
The purpose of this study was to determine students' perspectives on the world of work in the fieldwork internship program. The method used was descriptive quantitative. The sample for this study consisted of grade XII students who completed a fieldwork internship, and the data were obtained from questionnaire results. The researcher selected 77 students, namely, 31 from grade XII Agribusiness Plantation Crops, 26 from grade XII Visual Communication Design, and 20 from grade XII Motorcycle Engineering, as the sample. The results of this study indicate that the majority of students responded very positively to various aspects of the program. The average percentage of "strongly agree" and "agree" responses was dominant in each statement, with the combined figure exceeding 90% in almost all indicators. The school's fieldwork internship program was considered very practical and relevant by students. This program not only provided direct experience aligned with their competencies and majors but also increased students' readiness, self-confidence, and career insight. In addition, the fieldwork internship encouraged the development of technical and soft skills, such as problem-solving and an understanding of work ethics. It indicates that the fieldwork internship program has been running well and has successfully achieved its primary objective of bridging the worlds of education and work.